Assessing and addressing practitioner burnout: Results from an advanced practice registered nurse health and well-being study. Issue 1 (5th January 2021) - Kapu, April N.; Borg Card, Elizabeth; Jackson, Heather; Kleinpell, Ruth; Kendall, Jim; Lupear, Buffy Krauser; LeBar, Kiersten; Dietrich, Mary S.; Araya, Wendy A.; Delle, Janelle; Payne, Kate; Ford, Jaquelyn; et al.
ABSTRACT: Background: Numerous nursing and physician studies have reported the effects of workload, environment, and life circumstances contributing to burnout. Effects may include job dissatisfaction, poor quality of life, and associated negative patient outcomes. Although assessing clinician burnout to determine effective interventions has become a topic of great importance, there are minimal studies specific to advanced practice registered nurses (APRNs). Purpose: This single-center study was conducted to assess the prevalence and impact of APRN burnout and to recommend targeted interventions toward improvement of overall health and well-being. Methods: A cross-sectional, mixed methods design was used. The voluntary, anonymous survey examined perceptions of wellness, inclusion, social support, personal coping mechanisms, and status of burnout. Results: The 78-question survey was sent to 1, 014 APRNs (94%) and PAs (6%), with a 43.6% response rate ( n = 433); 76.4% were nurse practitioners. Participants were identified as currently experiencing burnout, formerly burned out, or never having experienced burnout. Profiles were developed, and similarities and differences between each group were compared. Of 433 respondents, 40.4% ( n = 175) reported having never experienced burnout, 33.3% ( n = 144) reported they had formerly experienced burnout, and 26.3% ( n = 114) reported they were currently experiencing burnout. Implications for practice: The results of the study identified that some APRNs report experiencing burnout at different times in their careers. Recommendations by participants to mitigate burnout included self-care, organizational promotion of health and well-being, career development, and leadership support. This study is one of the first to report on burnout among APRNs and potential interventions to build resilience; however, additional research is warranted.